Professional burnout syndrome in a group of nursing staff employed in a psychiatric hospital - Katarzyna Tomaszewska; Waldemar Porczak; Edyta Guty; Bożena Majchrowicz (Journal of Education, Health and Sport, 2023)
Nurses are one of the occupational groups most exposed to stress in the health care system. In their daily work, the staff of a psychiatric ward often encounters threats, aggression or unpredictability of patients' behavior. Employees, including nurses, often feel discomfort related to the treatment of patients admitted against their will, the need to use direct coercion. In psychiatry, it is also burdensome to participate in family matters of patients, to solve their problems. The group of factors recognized as stressful and causing psychological burden for nurses includes a large number of patients under their care, their serious condition as well as physical and verbal aggression of the patient and violence.